Evaluation of Electronic Commerce (E-Commerce) with SWOT Analysis as an Alternative Network Marketing at Agricultural Marketing - Nuray Kızılaslan; Tayfur Ünal (Turkish Journal of Agriculture: Food Science and Technology, 2015)
Compulsory competition occurring in the world trade has led the enterprises to different marketing system. Marketing problems seems to be a problem in Turkey rather than agricultural production problems. In this aspect, marketing alternatives are sought. E-commerce is a system with more opportunities in agricultural marketing. Increasing the applicability of this system in Turkey will eliminate many problems associated with marketing in agriculture. With an active use of E-commerce in agricultural marketing, it provides convenience at marketing products of agro-related industries agencies and producers and all country will have a potential market position. In this study, possibilities offered by e-commerce to the agricultural sector, opportunities, threats, deficiencies and contributions to agricultural sector have been addressed. Without the limitations of place and time via the internet and computers, establishing national and international supply and demand balance of e-commerce seems to play important roles in maintaining an active and alive marketing. Furthermore, it is an important tool in reducing agricultural marketing problems.